Gambaran Tipe Kepribadian Generasi Y di Indonesia - Seta Wicaksana; Estu Pratiwi Novasari; Sanchia Surya Janita (Jurnal Ilmiah Psikologi MIND SET, 2017)
The purpose of this research was to identify personality in Y Generation based on big five personality. Respondents of this research were 1286 Indonesian employee and college students, with age range18-37 years old (Y Generation). Personality was measured by NEO-PI-R Costa (Costa & Mcrae, 1992), which was developed by Humanika Consulting (2004). The value of coefficient reliability for NEO-PI-R Costa was 0.5 to 0.6. Data was analysed by descriptive quantitative methods. The analysis result showed that personality type of generation Y was low category on extraversion, openness to new experience, agreeableness, and conscientiousness personalities. Meanwhile, the type of personality neuroticism was in the category of average.